Federalismo cooperativo e direito à saúde no Brasil: uma análise sobre a distribuição infraconstitucional de competências entre os entes federativos - Gitrone, Denis Gustavo (Universidade do Vale do Rio dos Sinos, 2025)
This master's thesis investigates the right to health in Brazil, based on the following research problem: the infraconstitutional normative organization that distributes and regulates the administrative powers of Federative Entities meets the fundamental precept that, under the terms of the Constitution of the Federative Republic of Brazil, is health a right for everyone and a duty of the State? To address this issue, the study is divided into three distinct chapters, each corresponding to one of the specific objectives of the research. The first investigates the right to health in its theoretical and normative aspects. The second seeks to establish a kind of portrait of Brazilian public health. The last chapter focuses on the infraconstitutional distribution of powers between the federative entities and the Judiciary's handling of these issues. It was concluded that judicial intervention should be seen as a component of the health system, since the Judiciary can contribute to improving the Executive's decisions. This strengthens collaboration between the different powers and civil society in the search for the realization of the right to health. The methodological stance is phenomenological-hermeneutic.
Keywords: Ativismo judicial; Diálogos institucionais; Direito à saúde; Federalismo; Judicialização da política; Judicial activism; Judicialization of politics; Institutional dialogues; Right to health; Federalism; ACCNPQ::Ciências Sociais Aplicadas::Direito